Man and Woman Relationship In Anita Desai Novels: Exploring family problems and the separation of women in Anita Desai's novels (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The theme of man –woman relationship in Anita Desai’snovels reveals her accomplish craftsmanship. The novels of Anita Desai arenoted for the thoughtful inquisitive into the central life and feelings of thewomen, bounded by the restraints of the middle class. They are the explorationsof the family problems, which perhaps is the chief cause behind the separationof the women from their family.